2011
DOI: 10.1158/1078-0432.ccr-10-3271
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Attrition and Decreased Fetuin-A Levels Indicate Accelerated Biological Aging and Are Implicated in the Pathogenesis of Colorectal Cancer

Abstract: Purpose: Increasing chronological age is a risk factor for many types of cancer including colorectal. An understanding of the biology of aging and factors which regulate it may provide insight into cancer pathogenesis. The role of telomere biology in both the cancer and aging process could prove useful in this regard.Experimental Design: Using quantitative PCR, we determined telomere length in the peripheral blood leukocytes of 64 colorectal cancer (CRC) patients and 1,348 controls. We also measured telomere l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…determined that several oxidative-stress genes are linked with both telomere attrition and biological aging [ 76 ]. Moreover, decreased fetuin-A levels, a negative acute phase protein and mediator of redox homeostasis, have been associated with shortened leukocyte telomeres and increased risk for colorectal cancer and other diseases [ 16 ]. Correlations between shorter leukocyte telomeres and increased oxidative stress have also been reported in diabetics [ 24 , 28 ].…”
Section: Mechanisms Associated With Telomere Shorteningmentioning
confidence: 99%
See 1 more Smart Citation
“…determined that several oxidative-stress genes are linked with both telomere attrition and biological aging [ 76 ]. Moreover, decreased fetuin-A levels, a negative acute phase protein and mediator of redox homeostasis, have been associated with shortened leukocyte telomeres and increased risk for colorectal cancer and other diseases [ 16 ]. Correlations between shorter leukocyte telomeres and increased oxidative stress have also been reported in diabetics [ 24 , 28 ].…”
Section: Mechanisms Associated With Telomere Shorteningmentioning
confidence: 99%
“…Current evidence supports the idea that telomere length is associated with a number of chronic conditions including dyslipidemia [ 5 ], hypertension [ 6 , 7 ], atherosclerosis [ 8 , 9 ], stroke [ 10 ], coronary artery disease [ 11 , 12 ], myocardial infarction [ 13 ], and poor cardiovascular disease prognosis [ 10 , 14 , 15 ]. Decreased leukocyte telomere length is also present in patients with colorectal [ 16 , 17 ] and ovarian cancers [ 18 ]. It has been reported to be associated with high risks for gastric cancer [ 19 ], early onset of ovarian and breast cancers [ 20 , 21 ], as well as increased overall cancer incidence and mortality [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown CRC is associated with shortened PBL telomere length, longer PBL telomere length or no association at all. One has demonstrated an association 18 , two did not 19,20 and one showed an association with retrospectively but not prospectively obtained samples 21 and finally one has shown association with PBL telomere lengthening 22 . An explanation for the negative studies could be “colonoscopy bias”.…”
Section: Discussionmentioning
confidence: 92%
“…The following references discuss the various candidate peptides in more detail: alpha-1-antichymotrypsin [34], alpha-1-antitrypsin [35][36][37][38], alpha-2-HS-glycoprotein [20,[39][40][41][42], F. XIIIa [43], fibrinogen alpha chain [21], PF4 [21], prothrombin [43], vasodilator-stimulated phosphoprotein [44][45][46], and vinculin [47][48][49][50]. However, altered expression of these factors has not been associated with CRC and their known functions are not consistent with CRC pathology.…”
Section: Discussionmentioning
confidence: 99%